Combining ability of six agronomic traits in wheat (Triticum aestivum L.) - Scheeren, Pedro Luiz (1995)
The experiment was carried out in the field at the Estação Experimental Agronômica of Universidade Federal do Rio Grande do Sul, EEA-UFRGS, in Eldorado do Sul, Rio Grande do Sul, Brazil, in 1987. The objective of the experiment was to analyze the combining ability involving six traits in ten wheat genotypes. When the genetic aspects involved in the traits assessed were analyzed, it was observed that the additive effects had significant influence on the expression of the following traits: plant stature, peduncle length, number of fertile tillers per plant, number of fertile spikelets per spike, grain weight per plant, and maximum grain number per spikelet. Significant non-additive effccts for the traits peduncle length, number of fertile spikelets per spike and maximum grain number per spikelet were also identified.